Sustainable urban planning in the context of an ageing population - Kerbler, Boštjan (Journal for Geography, 2011)
Urban planning is facing major challenges in harmonizing of possible structural gaps between the built environment and ageing. The built environment is an important factor that affects the quality of human life, especially the elderly. Urban planning should therefore be sustained also in the context of an ageing society, since it plays an important role in enabling for older people to remain active members of society, especially local communities, in which they reside, despite their the ​​mobility, sensory and cognitive difficulties. Barrier‑free access to the built environment, use of transportation infrastructure and diversity of housing supply can positively affect the experience of ageing, and therefore discussed in this article.